Operational Planning in E-Commerce Companies â€œSimpel Omâ€ â€œPT Simpel Om Unggulanâ€ - Efa Hindarti; Edi Hamdi; Rhian Indradewa; Ferryal Abadi (Syntax Idea)
The development of Indonesian commercial property (PPKom) released by the Statistics Department of Bank Indonesia (BI) in the first quarter of 2022 welcomed 2022 as the year of revival of the Indonesian property sector. The annual performance (year on year) of the property (real estate) industry sector grew by 1.19% since the end of the COVID-19 pandemic. Apart from property growth, technological developments are increasingly simplifying and speeding up the transaction process, especially electronic shopping transactions ( eCommerce ) . The transition from the Analog to Digital era encourages all business sectors to be more creative in mastering market competition, one of which is the construction material supply and demand sector. PT Simpel OM Unggulan with the platform name "Simpel OM" is present as a material provider platform for the construction sector and a liaison between consumers and sellers with a 1x24 hour delivery commitment and free shipping which is the best solution in today's instant era.